Global war on terror : Bangladesh perspective - Seminar on Global War on Terror: Bangladesh Perspective (2007 : Dhaka, Bangladesh); Osmany, Mufleh R.; Kabir, Mohammad Humayun; Bangladesh Institute of International and Strategic Studies (Dhaka : Academic Press and Publishers Library in association with Bangladesh Institute of International and Strategic Studies, 2007)
Papers presented at the Seminar on Global War on Terror: Bangladesh Perspective, held in Dhaka, Bangladesh in 2007; organized by Bangladesh Institute of International and Strategic Studies.
Includes bibliographical references.
Keywords: Terrorism -- Bangladesh -- Congresses